(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Dental plaque is the sole reason for dental caries and periodontal disease. Few antibacterial agents might counterbalance the inadequate mechanical plaque removal. Antimicrobial agents are best indicated in secondary and tertiary prevention as the objectives are to restore health and to prevent disease recurrence. The rationale behind it is to prevent or delay subgingival recolonization by pathogenic microorganisms. Delmopinol is a chemical plaque control agent which can be used as an adjunct to mechanical plaque control. It is an antiplaque agent that aids in reduction of plaque and gingivitis while possessing the property of inhibiting the adhesion of oral microorganisms to the tooth surface. Long term use of such compound can preserve the biological environment of the oral cavity.